Evaluasi Pelaksanaan Sistem Blok dalam Kurikulum Pusat Keunggulan - Oka Kurniadi; Mukhlidi Muskhir (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2022)
This research was motivated by the low learning outcomes in programmed control system subjects, namely only 66% (21 students) while only 34% (11 students) completed. This is presumably due to the less than optimal implementation of the Block System in the Center of Excellence Curriculum in Class XI TOI Electrical Engineering Department at SMK Negeri 2 Payakumbuh. The purpose of this research is to implement the Block System in the Curriculum of the Center of Excellence in Class XI Electrical Engineering Department at SMK Negeri 2 Payakumbuh. This type of research is quantitative descriptive research, with the CIPP evaluation model (context, input, process, product). The population in this study were 32 students of class XI TOI Electrical Engineering Department at SMK Negeri 2 Payakumbuh. Data collection techniques using a questionnaire. The data analysis technique uses the percentage formula. The results of the evaluation study on the implementation of the Block System in the Center of Excellence Curriculum in Class XI TOI Electrical Engineering Department at SMK Negeri 2 Payakumbuh in terms of context, input, process, product were considered poor.